Age influence in growth of vinal (Prosopis ruscifolia Burkart.), in the Province of Santiago del Estero, Argentina - Giménez, Ana María; Ríos, N.; Hernández, P.; Moglia, J. G. (Instituto de Ecología, A.C., 2016)
Vinal (Prosopis ruscifolia) is a multi-purpose tree, halophyte, colonizer par excellence of unstable environments proved to flooding. The research objective of this work are: Analyseng the growth prospects of individual trees in relation to age, and estimate biological turn short. Fifteen trees of Prosopis ruscifolia, Mimosaceae, were selected from the natural forest of Loreto, San Martin Department, Santiago del Estero province, Argentina. Trees selection were based on the following criteria dominant canopy, healthy, with good form, more than 15 cm of DBH and free of defects. Transverse sections were obtained at different heights from 0,30, 1,30 m, and until the first branching. Growths rings were determined in four radii at north, south, east and west orientations. Rings width was measured with the Computerized Equipment ANIOL and the program CATRAS. Prosopis ruscifolia is a rapid growth tree in the Semi arid Chaco region, with ring average thickness of 5,66 mm (2,20-9,8). Minimum cut diameter is 25 cm, which is equivalent to 23 years. IMA and AI calculated by volume of stem reache the biological cut shift at the age of 45 years. The behaviour of this species in other growing conditions requires further study.